Epidemiology and Morbidity of Head Lice Infestation in Khorram-shahr County, Iran (2006-2009) - Hamid Kassiri; Ali Kasiri; Niusha Kasiri; Fahimeh Moeininejad (Shiraz University of Medical Sciences, 2015)
Background: Pediculosis capitis is a continuous common health problem worldwide. Pediculus capitis distributes quickly in overcrowded regions. The goal of the present research was to determine some epidemiological features of head lice infestation in Khorram-shahr County, southwestern Iran. Methods: This descriptive cross-sectional study was conducted on the patients with head lice infestation who referred to the Khorram-shahr Health Center during 2006 to 2009. The gold standard in the diagnosis of infestation was the detection of living nymphs, adults and/or nits on the scalp and hair. After the visual inspections with using a lens and the aid of an ordinary comb, cases were asked to complete a data gathering form containing some questions about demographic and epidemiologic features. The collected information was evaluated using SPSS software, version 11.5. Results: Totally, 1091 patients were infested with pediculosis capitis. The overall prevalence of head lice infestation during the four- year period was 0.73%. Girls were significantly more infested (87.2%) than boys (12.8%). Pediculosis capitis infestations were highest (46.2%) in subjects aged 6-10 and lowest in those aged less than six (6.4%). The majority of cases lived in the rural areas. The percentage of infestation in rural and urban patients was 59.2% and 40.8%, respectively. Nearly, 11.8% of the patients with head lice had a history of infestation. Most of the cases were found in the Autumn (35.8%). Conclusion: Girls were more frequently infested with Pediculus capitis than boys. It can also be concluded that head lice infestation is not highly prevalent in Khorram-shahr.